Globalization and the Shariah in Malaysia: a constitutional perspective on the legal effect of International law and treaties on Islamic religious laws - Mokhtar, Khairil Azmin (IIUM Press, 2009)
The International Human Rights Treaties that have been ratified by Malaysia are not prejudicial to the syariah and Islamic Religious legislations made by Federal legislature and State legislature. International instruments cited by some quarters to be the basis for declaring Syariah and its legislations void due their 'inconsistency' or 'in conflict' with international law on human rights are not binding on the Malaysian court and on executive and legislative bodies in the country. International law cannot override the Federal Constitution, which is the supreme law of the land. International law international treaties and conventions must be adopted as long as they are not in conflict with the Syariah as well as religious values and norms of other religion practiced in Malaysia. This is in line with the Rukun Negara which states that 'Belief in God' as one of the pillars of the nation. The view has been recognized by the Malaysian court in a recently decided case.